1995
DOI: 10.1136/vr.137.21.531
|View full text |Cite
|
Sign up to set email alerts
|

A study of mortality among suckler and dairy cows in Northern Ireland in 1992

Abstract: As part of an initiative aimed at reducing the number of cattle deaths in Northern Ireland, a survey of bovine mortality on a stratified random sample of farms and veterinary practices was carried out during 1992. In the farm survey, over 3500 deaths were reported from 1069 farms, with a further 237 farms reporting no deaths during the year. The estimated numbers of deaths of suckler cows and dairy cows were 5997 and 4246, respectively, giving an estimated annual mortality rate of 2.36 per cent for suckler cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
3
31
0
1
Order By: Relevance
“…Previous studies have identified that an increased proportion of purchased cows Raboisson et al, 2011), no pasture-grazing Burow et al, 2011;Dechow et al, 2011), larger herd sizes (Nørgaard et al, 1999;Smith et al, 2000;Raboisson et al, 2011) and lower herd average milk yield (Smith et al, 2000;, are all factors associated with increased MR. In contrast, Menzies et al (1995) did not find any effect of herd size on mortality and Miller et al (2008) found a small but consistent decrease in death frequency as herd size increased. Also, Nørgaard et al (1999) found an increase in mortality with increasing average milk yield.…”
Section: Introductionmentioning
confidence: 58%
“…Previous studies have identified that an increased proportion of purchased cows Raboisson et al, 2011), no pasture-grazing Burow et al, 2011;Dechow et al, 2011), larger herd sizes (Nørgaard et al, 1999;Smith et al, 2000;Raboisson et al, 2011) and lower herd average milk yield (Smith et al, 2000;, are all factors associated with increased MR. In contrast, Menzies et al (1995) did not find any effect of herd size on mortality and Miller et al (2008) found a small but consistent decrease in death frequency as herd size increased. Also, Nørgaard et al (1999) found an increase in mortality with increasing average milk yield.…”
Section: Introductionmentioning
confidence: 58%
“…In this review, the interval between sampling and receipt at the laboratory had no effect, possibly because of the small number of eye fluid samples received more than 48 hours after sampling and the difficulty with which a laboratory diagnosis of hypomagnesaemia can be made from eye fluid samples alone. Hypomagnesaemia was the most common diagnosis from the beef submissions; similarly, Menzies and others (1995) found that hypomagnesaemia was the main cause of death of suckler cows in Northern Ireland.…”
Section: Discussionmentioning
confidence: 93%
“…Dessa forma, é de suma importância estabelecer a prevalência das doenças causadoras de morte em rebanhos leiteiros de diferentes regiões, a fim de diminuir situações de risco e nortear a tomada de medidas profiláticas . Vários estudos sobre causas de mortes de vacas leiteiras foram realizados em diferentes países; contudo, a grande maioria determinou a causa da morte baseada em questionários submetidos aos proprietários ou veteriná-rios clínicos (Menzies et al 1995, Esslemont & Kossaibati 1997, Thomsen et al 2004. Estudos que avaliaram a causa da morte de vacas leiteiras através de exame de necropsia, como no presente trabalho são escassos (McConnell et al 2009, McConnell et al 2010, Thomsen et al 2012.…”
Section: Discussão E Conclusõesunclassified